2019
DOI: 10.1186/s13047-019-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Key concepts in children's footwear research: a scoping review focusing on therapeutic footwear

Abstract: Background Reports suggest that children with mobility impairment represent a significant proportion of the population living with a disability. Footwear is considered to be the key extrinsic factor affecting children’s gait and footwear modifications have been historically postulated to assist with locomotory difficulty. Although therapeutic footwear has been considered within the literature, there is a lack of consistency on terminology and paucity on the overall understanding. A scoping review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 187 publications
(254 reference statements)
0
40
0
3
Order By: Relevance
“…Database searches yielded 5003 unique articles ( Fig. 1) with 3 further papers found through screening the reference lists of related reviews sourced from the previous scoping review [24]. From these, 80 articles were identified as discussing children's therapeutic footwear with 23 articles identified for full-text eligibility screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Database searches yielded 5003 unique articles ( Fig. 1) with 3 further papers found through screening the reference lists of related reviews sourced from the previous scoping review [24]. From these, 80 articles were identified as discussing children's therapeutic footwear with 23 articles identified for full-text eligibility screening.…”
Section: Resultsmentioning
confidence: 99%
“…The types of therapeutic footwear interventions that were explored in the 13 studies fell into 2 of the previously defined groupings from the scoping review [24] corrective (n=3) and functional (n=10) ( Table 1). No studies explored the effects of accommodative therapeutic footwear for children.…”
Section: Therapeutic Footwear Interventionsmentioning
confidence: 99%
“… 55 However, this methodology may change due to a greater awareness of the results. 56 As a stepwise method that has previously been used to map concepts in a scoping review (eg, children’s therapeutic footwear), 57 textual narrative synthesis includes quality appraisal as part of the analysis, addressing limitations such as study bias and design. 58 The first step involves grouping the studies into subgroups.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 1–3 Correspondingly footwear has been used both historically and in modern healthcare practice as an assistive aid for children with mobility impairment. 4 5 However, a recent scoping review 6 highlighted that footwear as a clinical intervention for children lacks a common understanding of terms and definition as to the specifics of its clinical role. The development of recognised terms, definitions and characteristics of a healthcare intervention afford an understanding of how it should work, the value it should provide, who should benefit, how to measure its success, what risks are present and what is and is not included within the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The development of recognised terms, definitions and characteristics of a healthcare intervention afford an understanding of how it should work, the value it should provide, who should benefit, how to measure its success, what risks are present and what is and is not included within the intervention. 7 8 The scoping review 6 demonstrated that numerous terms have been used in the literature concerning clinical footwear interventions, including orthopaedic shoes, rehabilitative boots, modified shoes, supportive shoes and special shoes. Additionally, there was no clear definition of the clinical role and outcome measures to classify and group the range of available children’s footwear interventions.…”
Section: Introductionmentioning
confidence: 99%